Respuesta bioproductiva de Alevines de (Dormitator latifron) alimentados con diferentes niveles de proteína en dietas balanceadas - Rodriguez Castro, Lady Brigithe (2022)
This research was carried out in the experimental farm "La María," owned by the State Technical University of Quevedo, located at km. 7 ½ via Quevedo-El Empalme, Province of Los Ríos, the research lasted 63 days in which zootechnical and economic parameters were determined. They were studied balanced with three levels of protein, each treatment at different percentages of protein T1 (28%), T2 (32%) And T3 (36%), cages were used in which 10 fences of Chame were placed (Dormitator latifron) in 12 cages, biometrics were performed every 7 days analyzing the bioproductive behavior of the fry feeding them with the balanced for a period of 63 days, a Complete Design was used at Random (DCA) applying a statistical analysis of TUKEY for 3 treatments and 4 cage repeats. The fry went to an acclimatization state of 15 days feeding them with shrimp balance to 35% protein in which the fish were able to adapt to captivity, which was very beneficial for the fry providing greater resistance to diseases a better productive performance. At the end of the experiment it was noted that there are no significant differences between treatments in relation to the zootechnical and economic variables (P≥0.05) which details that the best treatment for its profitability is T1 (28%) of protein. Keywords: Alevín, Biomass, Diet, Protein, Dormitator Latifron